Analysis of the descriptor Roesser model with the use of the Drazin inverse - Kaczorek, Tadeusz (1932- ) (Zielona Góra: Uniwersytet Zielonogórski)
A method of analysis for a class of descriptor 2D discrete-time linear systems described by the Roesser model with a regular pencil is proposed. The method is based on the transformation of the model to a special form with the use of elementary row and column operations and on the application of a Drazin inverse of matrices to handle the model. The method is illustrated with a numerical example.
Keywords: Drazin inverse; descriptor; Roesser model; descriptor-time; 2D linear system